Budaya anti korupsi: Menanamkan nilai kejujuran dalam organisasi kemahasiswaan - fadhilah, adwa al (Maliki Interdisciplinary Journal, 2026)
Corruption is a serious problem that undermines the nation's hopes for social justice and prosperity. Efforts to eradicate corruption are often limited to government institutions, while small-scale corrupt behavior can thrive and be accepted within student organizations. The purpose of this study was to analyze various types of corrupt behavior within student organizations and to formulate strategies for teaching anti-corruption values ​​as a preventative measure. The approach used was a qualitative descriptive analysis based on literature review and direct observation within the university environment. The findings indicate that corrupt acts within student organizations fall into three main categories: falsification of Accountability Reports (LPJ), academic corruption behind the scenes (such as taking attendance and misusing permits), and misuse of time and violations of work ethics. As a solution, the implementation of the five core anti-corruption values honesty, caring, responsibility, simplicity, and fairness needs to be integrated into creative educational methods and involve active participation on campus. In conclusion, education that prioritizes anti-corruption in universities can be an effective long-term prevention strategy to end the culture of corruption and shape a future generation of leaders with integrity.